YH12852, a Potent and Selective Receptor Agonist of 5‐hydroxytryptamine, Increased Gastrointestinal Motility in Healthy Volunteers and Patients With Functional Constipation - Hyun A. Lee; Seol Ju Moon; Hyounggyoon Yoo; Mi Kyung Kim; Seong Bok Jang; Seoungoh Lee; Sohee Kim; Howard Lee (Wiley, 2021)
Gastrointestinal (GI) motility disorders are common, decreases quality of life, and imposes a substantial economic burden. YH12852 is a novel agonist of 5‐hydroxytryptamine for the treatment of GI motility disorders. This phase I/IIa study assessed the tolerability, pharmacodynamic (PD) and pharmacokinetic (PK) profiles of YH12852. In the multiple dose (MD) cohort, healthy subjects and patients with functional constipation were randomized and received orally YH12852 at 0.3, 0.5, 1, 2, or 3 mg or prucalopride 2 mg or their matching placebo, once daily for 14 days after breakfast. In the multiple low‐dose cohort (MLD), healthy subjects randomly received once‐daily oral doses of YH12852 at 0.05 or 0.1 mg for 14 days after breakfast. Questionnaires, gastric emptying breath test for PDs, and plasma samples for PKs were collected. In the MD cohort, a total of 56 subjects (29 healthy volunteers and 27 patients with functional constipation) were randomized, of whom 48 completed the study. In the MLD cohort, a total of 16 healthy subjects were randomized, and 15 subjects completed the study. YH12852 increased the average weekly frequency of spontaneous bowel movements and loosened the stool. In addition, YH12852 increased quality of life satisfaction, and decreased severity of constipation symptom and GI symptoms. YH12852 was safe and well‐tolerated up to 3 mg and showed nearly dose proportional PKs. In conclusion, YH12852 was safe and enhanced GI motility. YH12852 can be developed as an effective treatment option for GI motility disorders, including functional constipation. Further studies are warranted to confirm this possibility.